Indexing, the art of : a guide to the indexing of books and periodicals - Knight, G. Norman (London ; Boston : Allen & Unwin, 1979)
The aim of the book is to provide authors with the necessary information on how to provide index for their works.
Includes bibliographical references and index.
oo 22/01/2019
Loans
Keywords: Indexing